Islamic Criminal Law in a Plural Legal Order: A Systematic Literature Review of Qanun Jinayah Effectiveness in Aceh, Indonesia - Yuni Roslaili; Fauzan, Faisal; Suparwany (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2025)
The Qanun Jinayah represents Aceh’s distinctive model of Islamic criminal law within Indonesia’s secular constitutional framework. Its implementation has generated considerable debate regarding legitimacy, effectiveness, and alignment with national and international human rights standards. Despite extensive discourse, existing studies remain fragmented and largely descriptive, lacking an integrated analytical framework to evaluate its real societal impact. This study addresses that gap by systematically reviewing literature published between 2014 and 2024 using the PRISMA methodology. Relevant sources were identified through Google Scholar and managed with Mendeley for screening, duplication removal, and thematic classification. Nine empirical and conceptual studies met the inclusion criteria. The findings reveal a dual narrative: while the Qanun Jinayah demonstrates normative effectiveness in reflecting Islamic principles and supporting moral governance, institutional and socio-cultural effectiveness remains partial due to weak law enforcement capacity, inconsistent procedural alignment with national law, and limited protection of individual rights. This review contributes theoretically by proposing a multi-dimensional effectiveness framework that integrates normative, institutional, and socio-cultural dimensions offering a more holistic tool for assessing hybrid Islamic-secular legal systems. The study concludes that while Qanun Jinayah upholds regional autonomy under Law No. 44/1999 and Law No. 11/2006, substantive reform is urgently required to enhance institutional legitimacy and human rights compliance. The findings hold significant implications for scholars and policymakers seeking to reconcile Islamic criminal law with Indonesia’s plural legal order and for comparative research on localized Sharia implementation in plural legal contexts.